2018
DOI: 10.4049/immunohorizons.1800070
|View full text |Cite
|
Sign up to set email alerts
|

The Commensal Neisseria musculi Modulates Host Innate Immunity To Promote Oral Colonization

Abstract: Neisseria musculi, isolated from the oral cavity of wild-caught mice, does not colonize most inbred mouse strains. N. musculi does weakly (50%) colonize C57BL/6J (B6) mice but readily colonizes CAST/EiJ (CAST) mice. In this study, we examined whether differences in the CAST and B6 host response could elucidate mechanisms governing N. musculi colonization. In vivo stimulation of B6 or CAST splenocytes with wild type (WT) Neisseria or Escherichia coli LPS showed that CAST mice had a blunted inflammatory response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 27 publications
4
9
0
Order By: Relevance
“…Inactivation of immunosuppression by UV-killing and not heat-killing indicated the possible involvement of nucleic acids as the mediating factor. Similar mechanisms have previously been observed [40], with high levels of double-stranded RNA in lactic acid bacteria associated with stimulation of interferon-β production, resulting in protective effects in a murine colitis model [41]. An absence of a heatlabile element would suggest that the immunomodulation observed here was not mediated by a protein.…”
Section: Discussionsupporting
confidence: 83%
“…Inactivation of immunosuppression by UV-killing and not heat-killing indicated the possible involvement of nucleic acids as the mediating factor. Similar mechanisms have previously been observed [40], with high levels of double-stranded RNA in lactic acid bacteria associated with stimulation of interferon-β production, resulting in protective effects in a murine colitis model [41]. An absence of a heatlabile element would suggest that the immunomodulation observed here was not mediated by a protein.…”
Section: Discussionsupporting
confidence: 83%
“…Further studies have shown that IL-6 expression is increased from human dental pulp cell cultures stimulated with Prevotella intermedia lipopolysaccharide 42 . In addition, Neisseri a has been demonstrated to suppress IL-6 production and our associations have indeed revealed that abundance of oral Neisseria is inversely correlated to IL-6 concentration 43 . Taken together, numerous studies have clearly demonstrated that oral bacteria utilize cytokines to sense the host environment and there is a dynamic interplay between both.…”
Section: Discussionsupporting
confidence: 65%
“…Neisseria spp. has been reported to regulate innate immune response and cytokine production in experimental infection models [57]. Our study suggested that pulmonary Neisseria decreased in the model group compared with the control group and increased after drug intervention.…”
Section: There Is a Significant Relationship Between Gut-lung Axis Mi...supporting
confidence: 46%